TRANSFORMASI ETOS KERJA DAN PENGENTASAN KEMISKINAN MELALUI PENDIDIKAN ISLAM HOLISTIK - Syaidah, Khasnah; Dawam, Ainurrafiq (STIT AL-AMIN KREO TANGERANG, 2024)
This study aims to describe the contribution of Islamic education in alleviating poverty. This study uses a descriptive analysis method. Data collection uses library research techniques by referring to written data published in the form of books, encyclopedias, and scientific journals that are relevant to the theme taken. Furthermore, coding is carried out and continued by analyzing categorically and poured into a narrative in a logical, systematic and reflective manner. The results of the study indicate that Islamic education plays a crucial role in poverty alleviation by implementing holistic learning methods, techniques, and strategies. Islamic education must pay attention to various aspects such as the biological and genetic environment of students, physiological and technical needs, and their neurological and rational development. In addition, psychological and spiritual aspects must be considered to form a strong work ethic. With this holistic approach, Islamic education not only educates individuals to be intelligent and skilled, but also forms perfect human beings who have integrity and the ability to overcome economic challenges, thus significantly contributing to poverty alleviation.